Подставляем вместо х значение -5 и находим q: 3*(-5)²+10*(-5)+q=0; 75-50+q=0; 25+q=0; q=-25; 3x²+10x-25=0; D=10²-4*3*(-25)=100+300=400=20²; x=(-10-20)/(2*3)=-5; x=(-10+20)/(2*3)=5/3; 3x²+10x-25=3(x+5)(x-5/3)
1)=(по основанию 5) log(4+x)(1+2x)= log 9 4+x>0 x>-4 и 1+2x>0 x>-1/2, т е х>-1/2 4+8x+x+2x²=9 2x²+9x-5=0 x1,2=((-9+-√(81+40))/4= (-9+-11)/4, x1=-5-не удовлетворяет x>-1/2 x2=1/2-ответ 2) 1+x>0 x>-1и 2+x>0 x>-2, т е х>-1 = (по основанию 2)log(1+x)(2+x)=1 x²+x+2x+2=2, x²+3x=0 x1=0, x2=-3-не удовлетворяет x>-1 x=0- ответ 3) x-2>0 x>2 и x+1>0 x>-1, т е x>2 = (по основанию 2)log(x-2)(x+1)=2, x²+x-2x-2=4, x²-x-6=0, x1,2=(1+-√(1+24))/2=(1+-5)/2, x=3- ответ